OPTIMALISASI DAN PENDAMPINGAN PENGGUNAAN TRANSAKSI DAN PEMBAYARAN DIGITAL PADA UMKM DI DESA KARYAMEKAR, GARUT, JAWA BARAT - Popon Rabia Adawia; Ashri Ramadhani; Muhammad Ridwan; Asep Solihin; Zahra, Zahra (POLITEKNIK LP3I JAKARTA, 2025)
The development of digital technology has transformed the national economic landscape, including transaction and payment patterns in the micro, small, and medium enterprise (MSME) sector. However, in rural areas such as Karyamekar Village, Garut, West Java, most MSMEs still conduct transactions conventionally and have not fully utilized digital payment systems. This situation results in inefficient transaction processes, poorly managed financial records, and limited market expansion opportunities. This community service program aims to improve MSMEs' digital literacy and competency through training and mentoring on the use of digital transactions and payments. The methods used include interactive training, hands-on workshops on the use of digital payment applications (such as QRIS and digital wallets), and a month of intensive mentoring on implementing these systems in daily business activities. This activity is expected to improve MSMEs' capabilities in conducting cashless transactions, improving financial recording systems, and increasing business efficiency. Furthermore, the program aims to foster a sustainable village digital economy ecosystem through the formation of local digital mentoring groups. Overall, this program is expected to serve as a model for community empowerment based on digital transaction processing that can be replicated in other rural areas. Through this activity, universities play an active role in supporting the national policy of